Profile Of Leper Patients With Reversal Reactions In Irj Skin And Genitals Morbus Hansen Division Dr Soetomo Regional Hospital - Putri, Dyfe Alisya; Widia, Yuri; Alinda, Medhi Denisa; Romadhon, Pradana Zaky (Journal of Neonatal Surgery, 2025)
Leprosy (leprosy) is still a public health problem in Indonesia, with East Java as one of the provinces with a high number of cases. Reversal reactions (type 1 reactions) are immunological complications in leprosy patients and can cause permanent nerve damage if not treated properly. This study aims to determine the clinical and epidemiological profile of leprosy patients with reversal reactions who seek treatment at the Skin and Venereology Outpatient Installation at RSUD Dr. Soetomo Surabaya for the period January 2015 to September 2024. Retrospective descriptive research by analyzing medical record data of leprosy patients who experienced reversal reactions at the Skin and Venereology Outpatient Installation at Dr. RSUD. Soetomo Surabaya from January 2015 to September 2024. Data collected includes demographic characteristics (age, gender, occupation, address), type of leprosy, time of reaction, clinical manifestations, degree of disability, and therapy modalities. The number of leprosy patients based on the results of research on patient medical records for the period 2015 to 2024 was 14,056 patients, an increase in the number of patients compared to previous years, of this number of patients with reversal reactions were 222 patients (1.58%) while type 2 (erythema nodosum leprosy) as many as 13,834 patients (98.42%). The conclusion of this study is that reversal reactions occur more often in patients with multibacillary leprosy (MB) and generally in adult men, more precisely over 17 years. The incidence of reversal reactions was also found more frequently in patients who had undergone treatment Multidrug Therapy (MDT), with most reactions occurring 1-3 years after treatment begins. Treatment of leprosy with a reversal reaction requires careful monitoring and multidisciplinary management involving a variety of therapies, including the use of appropriate medications as well as additional therapies to reduce inflammation and improve the patient's quality of life.